Binding of Natural Inhibitors to Respiratory Complex I - Jonathan Schiller; Volker Zickermann (MDPI AG, 2022)
NADH:ubiquinone oxidoreductase (respiratory complex I) is a redox-driven proton pump with a central role in mitochondrial oxidative phosphorylation. The ubiquinone reduction site of complex I is located in the matrix arm of this large protein complex and connected to the membrane via a tunnel. A variety of chemically diverse compounds are known to inhibit ubiquinone reduction by complex I. Rotenone, piericidin A, and annonaceous acetogenins are representatives of complex I inhibitors from biological sources. The structure of complex I is determined at high resolution, and inhibitor binding sites are described in detail. In this review, we summarize the state of knowledge of how natural inhibitors bind in the Q reduction site and the Q access pathway and how their inhibitory mechanisms compare with that of a synthetic anti-cancer agent.